PENGARUH EDUKASI MEDIA POSTER TENTANG PENGENDALIAN HIPERTENSI TERHADAP PENGETAHUAN PASIEN HIPERTENSI (Jurnal Kesehatan Siliwangi, 2023)
Background: Non-communicable diseases or PTM are the cause of almost 70% death in the world. One of the non-communicable diseases is hypertension. West Java Province itself has a very high prevalence of hypertension at 39.60% (Ministry of Health, 2019). West Java Province has the highest hypertension cases in Indonesia, ranking second. And based on data on the health profile of the City of Bandung in 2020 in the Gede Bage District, the estimated number of hypertension sufferers aged 15 years and over is quite large, namely 11,085 people (Bandung City Health Office, 2020). Therefore, it is necessary to control hypertension in hypertensive patients by providing poster media education about hypertension control through poster media.Purpose: To determine the effect of poster media education on controlling hypertension on the knowledge of hypertension patients in Posbindu, Rancabolang Village, Gedebage District, Bandung City.Methods: This study used a quasi-experimental design with a one group pretest – posttest without control design to a sample of 59 hypertensive patients in a population of 141. Data analysis used the Paired T-test to prove the research hypothesis.Results: The average score of respondents' knowledge before being given poster media was 63.90. The average score of respondents' knowledge after being given poster media was 84.58. The percentage increase in knowledge is 20.678%. The p value on the knowledge of respondents before and after being given poster media was (p = 0.000).Conclusion: There was a significant increase in knowledge after being given poster media education about hypertension control on the knowledge of hypertension patients in Posbindu, Rancabolang Village, Gedebage District, Bandung City.